(untitled) (Bangladesh Medical Journal, 2026)
Decompensated cirrhosis is associated with substantial morbidity and mortality. The Child-Turcotte-Pugh (CTP) and Model for End-Stage Liver Disease (MELD) scores are established tools for severity assessment, but inexpensive adjunctive biomarkers may be useful in resource-limited settings. Serum ferritin, an iron-storage protein and acute-phase reactant, may reflect inflammation, hepatocellular injury, and worsening liver disease.Materials and Methods: This cross-sectional study was conducted at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from April 2021 to March 2022. A total of 33 patients with decompensated liver cirrhosis were enrolled consecutively. Patients were categorized by ferritin level (<200, 200-400, and >400 ng/mL). Correlation was assessed using Spearman’s rank test. Multivariable analyses were performed using binary logistic regression for high MELD score (>15) and multiple linear regression for continuous MELD score, adjusting for age, sex, serum bilirubin, and serum albumin. A p-value <0.05 was considered statistically significant. Results: The mean age was 52.7 ± 14.07 years; 63.6% were 41-60 years old, and 72.7% were male. Hepatitis B virus was the commonest etiology (45.5%), followed by cryptogenic cirrhosis (24.2%) and hepatitis C virus (21.2%). Ascites was present in 97.0%, jaundice in 48.5%, hepatic encephalopathy in 33.3%, and anemia in 57.6%. Serum ferritin correlated strongly with CTP score (r=0.70, r²=0.49, p<0.001) and moderately with MELD score (r=0.50, r²=0.25, p<0.001). Across ferritin categories, grade 3 ascites increased from 12.5% to 25.0% and 70.6% (p=0.014), prothrombin time from 13 to 15 and 21 seconds (p=0.024), MELD score from 13.75 ± 5.85 to 20.13 ± 6.40 and 22.71 ± 5.03 (p=0.003), and CTP score from 8.00 ± 1.19 to 9.63 ± 1.85 and 11.18 ± 1.70 (p<0.001). In multivariable logistic regression analysis, serum ferritin >200 ng/mL was independently associated with a high MELD score (adjusted OR 5.92; 95% CI: 1.03–33.98; p=0.046). Serum bilirubin was also independently associated with a higher MELD score (p=0.037), while serum albumin showed an inverse association (p=0.031). In multiple linear regression, serum ferritin remained a significant independent predictor of MELD score (β = 0.38; p=0.021), with the model explaining 42% of the variance (adjusted R² = 0.42). Conclusion: Serum ferritin was significantly associated with CTP and MELD scores and with clinical markers of decompensation. It may serve as an accessible supplementary biomarker for severity assessment in decompensated cirrhosis, but its nonspecific inflammatory nature requires interpretation alongside established scoring systems. Bangladesh Med J. 2025 Sept; 54(3): 1-8